If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 12n = 13n + 4 Reorder the terms: 12 + 12n = 4 + 13n Solving 12 + 12n = 4 + 13n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-13n' to each side of the equation. 12 + 12n + -13n = 4 + 13n + -13n Combine like terms: 12n + -13n = -1n 12 + -1n = 4 + 13n + -13n Combine like terms: 13n + -13n = 0 12 + -1n = 4 + 0 12 + -1n = 4 Add '-12' to each side of the equation. 12 + -12 + -1n = 4 + -12 Combine like terms: 12 + -12 = 0 0 + -1n = 4 + -12 -1n = 4 + -12 Combine like terms: 4 + -12 = -8 -1n = -8 Divide each side by '-1'. n = 8 Simplifying n = 8
| 9-18u=-13-16u | | x-9x=1-5x | | 14=3(d-10)+2 | | -7x+6=-x-5 | | -2-5x=7x+2 | | 14v-20=13v | | -3+14h=10+15h | | -8x=-x-3 | | 7k=9k+18 | | f(x)=140X | | 8x+8=-2+4x | | 3(2+66)=186 | | -2+5x=8x | | tgx/4=-1/2 | | 193.408x^4*729.891x^3*302.17x^2=6000 | | 3cosa-3-4sina=0 | | 688850/15 | | an=5n+3 | | (6x+9)-2(2x-5)=38 | | X^3(2x^2+4x)= | | (X+y)(dx-dy)=dy+dx | | 9x+6=6x-12 | | 9-4(5x-3)=1 | | 3cos^2x/3-3=4sinx/3 | | 3.51/4 | | 5/250=d/300 | | x+5.67y=780 | | 6+0=-2y | | kx^3=5x+2 | | lny+4x=x+3lnx | | 5x/10=13x-10 | | 35x+23y=16xy |